Simulation via instant messaging – Birmingham advance (SIMBA): an innovative simulation-based learning model that helped to keep medical education continue during the COVID-19 pandemic. (2021) - Morgan, Georgia; Ooi, Emma; Hanania, Thia; Davitadze, Meri; Zhou, Dengyi; Blaggan, Parisha
No abstract available